Legal regulation of culture of Ukraine: on the materials 90-s of the XX century - Скрипчук, Г. В. (Problems of legality, 2014)
The author investigates the formation of the legal framework of contemporary Ukrainian culture, original official documents, which ensure the formation of the sphere of culture in Ukraine are analyzed in this article. The state budget of Ukraine by years has been researched in more detail, the analysis of the laws of Ukraine «On Libraries and Librarianship», «On Museums and Museology», «On Cinematography» and so on has been performed.